The mixed alloyed chemical composition of chloro-(chloro)n-boron subnaphthalocyanines dictates their physical properties and performance in organic photovoltaic devices. Issue 24 (3rd June 2016) - Dang, Jeremy D.; Josey, David S.; Lough, Alan J.; Li, Yiying; Sifate, Alaa; Lu, Zheng-Hong; Bender, Timothy P.
Abstract : We have determined that chloro-boron subnaphthalocyanine (Cl-BsubNc) is a mixture of products with random amounts of chlorination in the bay position. We have developed chemical processes to varying the amount of chlorination. Abstract : Chloro-boron subnaphthalocyanine (Cl-BsubNc) has recently attracted significant interest as a light-harvesting and charge transporting material in organic photovoltaic devices (OPVs) by enabling an 8.4% efficient planar heterojunction OPV cell. We present herein a variety of experimental data that supports the conclusion that Cl-BsubNc, whether synthesized via literature methods or our in-house methods or purchased commercially, is actually a mixed alloyed composition of Cl-BsubNcs with random amounts of chlorination at the bay position(s) of the BsubNc macrocyclic structure which we hereafter will refer to as Cl–Cl n BsubNc(s). We outline our efforts to develop alternative chemical processes, whereby we did obtain samples with lower and higher amounts of bay position chlorination. However, we were unable to obtain a pure, non-bay chlorinated sample of Cl-BsubNc. The positions and frequencies of the peripheral chlorine atoms were determined via single crystal X-ray crystallography of two different mixed alloyed compositions of Cl–Cl n BsubNc samples and MS and XPS analysis of all Cl–Cl n BsubNc samples. The photo- and electro-physical properties were found to differ amongst the Cl–Cl n BsubNc samples with varying amounts of chlorination. These differences also translated into varying performance within planar heterojunction OPVs, whereby a mixture of Cl–Cl n BsubNcs with lower amounts of chlorination produced less efficient OPVs (albeit with a higher open circuit voltage) compared to a mixture with higher amounts of chlorination. Additionally, an in-house made sample of Cl–Cl n BsubNc, with the highest level of bay position chlorination, yielded the best performing OPVs through an improved fill factor. A commercial sample of Cl–Cl n BsubNc also yielded OPVs with efficiencies equivalent to a Cl–Cl n BsubNc sample prepared in our laboratory. This mixture of Cl–Cl n BsubNcs is therefore likely to be present in the reported 8.4% efficient OPV device. Our results therefore offer a cautionary note that the Cl-BsubNc samples used within the existing literature are likely not a pure chemical composition but are rather mixtures of Cl–Cl n BsubNcs with bay position chlorination. Our findings clarify the previous literature results on the chemistry of Cl-BsubNc, firm up the photo- and electro-physical properties of these materials, and offer additional insight into their application as functional materials in efficient OPVs.